Prevalence of Dental Fear and Anxiety among School Children in Zawia City, Libya - Amani Barka; Lubna Abdalrahman; Nebras Hamida; Rawiyah Alshaybani; Tahani Alfahim (AlQalam Journal of Medical and Applied Sciences, 2024)
Odontophobia, also known as dental fear and anxiety (DFA), is a type of phobia that can negatively affect the dental and oral health of people who experience it. This phobia has psychosocial characteristics that make it complex to address in dental practice. Dealing with dental fear is a challenging issue in dentistry for various reasons. Although this issue has been studied in children for quite some time around the world, no such studies have been conducted in Zawia, Libya. Therefore, this study aimed to determine the prevalence of dental fear and anxiety (DFA) among pupils aged 5 to 12- years in public and private schools in Zawia City. A cross-sectional survey was conducted in Zawia City over three months. In the survey, 205 students were randomly selected from several private and public schools. All participants were given a self-reported questionnaire containing ten closed-ended questions about DFA. After collecting the data, the results were analyzed based on gender and school type and entered into a Microsoft Excel sheet for further analysis. Results of the study showed that 31.71% of all pupils experienced dental fear and anxiety (DFA). Furthermore, the slight variations in fear levels based on school type indicate that the school environment may influence a pupil’s perception of dental visits. Most private school students experienced DFA during physical contact with their dentists and upon seeing dental anesthesia injections. Whereas pupils attending government schools experienced DFA when hearing voices during treatment. Across all areas studied, female students reported slightly higher levels of anxiety than male students. Based on the survey results, it is evident that many pupils experience high levels of dental fear and anxiety (DFA). This highlights the need for intervention and attention in such situations, as DFA can significantly affect a pupil’s dental experience and oral health outcomes. Therefore, it is essential to address these fears and anxieties to improve the overall dental experience of pupils and promote better oral health رهاب الأسنان، والذي يُعرف أيضًا باسم الخوف والقلق من طب الأسنان، هو نوع من الخوف الذي يمكن أن يؤثر سلبًا على صحة الأسنان والفم للأشخاص الذين يعانون منه. لهذا الرهاب خصائص نفسية-اجتماعية تجعله معقدًا للتعامل معه أثناء ممارسة أو تقديم خدمات طب الأسنان. التعامل مع رهاب الأسنان هو أمر صعب في طب الأسنان لأسباب متعددة. على الرغم من أن هذه المشكلة قد تمت دراستها لدى الأطفال في جميع أنحاء العالم منذ فترة طويلة، لم تُجرَ مثل هذه الدراسات في الزاوية، ليبيا. لذلك، هدفت هذه الدراسة إلى تحديد مدى انتشار خوف و رهاب الأسنان (DFA) بين الطلاب الذين تتراوح أعمارهم بين 5 و12 عامًا في المدارس العامة والخاصة في مدينة الزاوية. أُجريت دراسة مقطعية في مدينة الزاوية على مدى ثلاثة أشهر. في الدراسة، تم اختيار 205 طالبًا عشوائيًا من عدة مدارس خاصة وعامة. تم إعطاء جميع المشاركين استبيانًا ذاتي يحتوي على عشر أسئلة ذات إجابات محددة و مغلقة" بنعم أو لا " عن خوف و رهاب الأسنان (DFA). بعد أن تم جمع البيانات، تم تحليل النتائج على أساس الجنس ونوع المدرسة وإدخالها في ورقة بيانات Microsoft Excel للمزيد من التحليل. أظهرت نتائج الدراسة أن 31.71% من جميع الطلاب عانوا من خوف و رهاب الأسنان(DFA). علاوة على ذلك، فإن التباينات الطفيفة في مستويات الخوف على أساس نوع المدرسة تشير إلى أن البيئة المدرسية قد تؤثر على تصور الطالب لزيارات طبيب الأسنان. عانى معظم طلاب المدارس الخاصة من الخوف والقلق من طب الأسنان (DFA) أثناء التواصل الجسدي مع أطبائهم الأسنان وعند رؤية حقن التخدير السني. في حين عانى الطلاب في المدارس الحكومية من الخوف والقلق من طب الأسنان (DFA) عند سماع الأصوات أثناء العلاج. في جميع المجالات التي تمت دراستها، أفادت الطالبات بمستويات قلق أعلى قليلاً من الطلاب الذكور. بناءً على نتائج الاستبيان، من الواضح أن العديد من الأطفال يعانون من مستويات عالية من الخوف والقلق من طب الأسنان (DFA). ويسلط هذا الأمر الضوء على الحاجة إلى التدخل والاهتمام في مثل هذه المواقف، حيث يمكن أن يؤثر الخوف والقلق من طب الأسنان (DFA) بشكل كبير على تجربة الطالب مع طب الأسنان ونتائج صحة الفم. لذلك، من الضروري معالجة هذه المخاوف والقلق لتحسين التجربة الشاملة لطب الأسنان للأطفال وتعزيز صحة الفم